3D numerical modelling of turbulent biogas combustion in a newly generated 10 KW burner. Issue 1 (February 2018) - İlbaş, Mustafa and Şahin, Murat and Karyeyen, Serhat
Abstract: This study concentrates on the 3D numerical modelling of combustion of different biogases in a generated burner and combustor. The main goal of this study is to investigate the combustion characteristics (such as temperature and emissions) of biogases through a combustor due to depletion of natural gas. Moreover, the effect of the preheated air on flame temperatures of biogases have been studied in the present study. Finally, the effect of H2 S amount in biogas on SO2 emissions has been investigated within these predictions. The numerical modelling of turbulent diffusion flames has been performed by using the standard k–ε model of turbulent flow, the PDF/Mixture Fraction combustion model and P-1 radiation model in the combustor. A CFD code has been used for all predictions. Temperature gradients have been determined on axial and radial directions for better understanding combustion characteristics of biogases. Modelling has been studied for thermal power of 10 kW and excess air ratio of λ = 1.2 for each biogas combustion. The first finding is that combustion of biogases is possible via the newly generated burner. Moreover, the results show that the one of biogas is very close to methane in terms of temperature distributions in the combustor due to including high amount of methane compared to other biogases. It is also concluded that the flame temperatures of biogases increase with preheating the combustion air as expected. It is finally revealed that SO2 emissions increase as amount of H2 S in biogas is increased through the combustor. Highlights: The newly generated burner has been described in detail. The PDF/Mixture Fraction combustion model, standard k-Ɛ turbulence model and P-1 radiation model have been used. Temperature and emission distributions of the biogases have been obtained. The effects of the preheated air and H2 S amount in the biogases have been investigated.